Development of Underwater Monitoring Wireless Sensor Network to Support Coral Reef Observation - Tsuyoshi Suzuki; Kazuki Kato; Emi Makihara; Takafumi Kobayashi; Hitoshi Kono; Kei Sawai; Kuniaki Kawabata; Fumiaki Takemura; Naoko Isomura; Hideyuki Yamashiro (International Journal of Distributed Sensor Networks)
We have been developing a wireless sensor network system to support coral ecological system survey activities. This paper studies the required functions of a wireless sensor node for gathering information on underwater environmental conditions. For this purpose, a prototype sensor node is developed to clarify necessary functions through a practical experiment. In this paper, the hardware configuration of a latest prototype of wireless sensor node is described. The design of this prototype was based on our previous experiments and the comments of coral reef researchers. We conducted practical field experiments to observe the coral reefs along the Okinawa coast in Japan by using the prototype. Moreover, a browsing system of gathered information by the sensor network is described. Finally, we discuss the experimental results and the required functions of the sensor node for the future research.